Enzymatic and site-specific ligation of minimal-size tetrazines and triazines to proteins for bioconjugation and live-cell imaging - Baalmann, Mathis; Ziegler, Michael J.; Werther, Philipp; Wilhelm, Jonas; Wombacher, Richard (Bioconjugate chemistry, 2019)
Diels-Alder reactions with inverse electron demand (DAinv) have emerged as an indispensable tool for bioorthogonal labeling and the manipulation of biomolecules. In this context, reactions between tetrazines and strained dienophiles have received attention because of high reaction rates. Current methods for the DAinv-mediated functionalization of proteins suffer from slow reactivity, impaired stability, isomerization, or elimination of the incorporated strained dienophiles. We report here a versatile platform for the posttranslational, highly selective, and quantitative modification of proteins with stable dienes. New synthetic access to minimal size tetrazine and triazine derivatives enabled us to synthesize tailored diene substrates for the lipoic acid protein ligase A (LplA) from Escherichia coli, which we employ for the rapid, mild, and quantitative bioconjugation of proteins by DAinv. The presented method benefits from the minimal tag size for LplA recognition and can be applied to proteins from any source organism. We demonstrate its broad suitability by site-specific in vitro protein labeling and live cell labeling for fluorescence microscopy. With this work we expand the scope of DAinv bioorthogonal chemistry for site-specific protein labeling, providing additional experimental flexibility for preparing well-defined bioconjugates and addressing biological questions in complex biological environments.